Educational Guidelines Derived from Occasions of some Quranic Chapters: An Analytical Study - Al-Dhaban, Abdullah Fayez Dhaban (Journal of Educational and Psychological Sciences, 2023)
The current study aims to analyze the educational implications inferred from the occasions of the surahs from Surah Al Bayyinah to Surah Quraysh. To achieve these objectives, the researcher adopted the descriptive- analytical approach in the derivation, by referring to the Holy Quran and collecting the verses related to it, and then deriving the educational implications from it. Out of the most important results that the researcher has reached are the following: The deep understanding of the faith educational implications of the occasions of the Surahs has a good effect on individual in this world and the Hereafter. Recognizing social educational implications of occasions of the surahs have positive impact on individual and society, and that psychological educational implications of the occasions of surahs are interested in some of the effects and aspects that affect one’s soul. Educational teachers have a basic role in building the educational and learning process and familiarity of the educational implications and methods, which produce positive effects in the (faith, social, and psychological) aspects. The researcher recommends the necessity to know and learn the faith educational implications of the occasions of surahs for their good return in the field of education and instruction. A study related to the social educational implications of the occasions of surahs should be developed because it touches the individual and society and the significance of studying and learning the psychological educational implications of the occasions of the surahs for their connection in the education and instruction field. Further, educational teachers should strive towards develop themselves to be able to mix between the faith and psychological aspects, as well as the educational aspects that serve individuals and community.